Performance Analysis of Production Forest Management Unit (PFMU) of Dharmasraya District, West Sumatra Province - Mahdi, Mahdi; Yonariza, Yonariza; Yuerlita, Yuerlita; Yurike, Yurike; Syafruddin, Yudha Saktian (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
The Production Forest Management Unit (PFMU) in Dharmasraya is the operational implementing organization of the Forest Service in the field and carries out forest management up to the site level (block / footprint). However, the successful management of the PFMU Dharmasraya cannot be separated from the dynamics of existing problems, such as conflicts between the government and the community around the forest area, the high level of occupation of the forest area by the community and claims of customary rights to the forest area, completion of the boundary process, the lack of good human resources quantity and quality and still weak security guarantees of investing in the PFMU area. The purpose of this study is to analyze the development performance of the Dharmasraya PFMU in the management and implementation of forestry programs at the site level. This study uses criteria and indicators from Forest Watch Indonesia version 2.0. The results showed the value of the development/development PFMU Dharmasraya index was at a moderate level with a value of 2.08. This means that as a forest manager at the site level, PFMU Dharmasraya is quite ready in realizing its functions and duties. Some criteria that need to be considered for improvement are organizational capacity, conflict resolution, investment mechanisms, and stability of the forest management unit area to be strengthened to ensure operation at the site level.